THE CRITICAL ROLE OF FINANCIAL PERFORMANCE IN SHAPING CAPITAL EXPENDITURE DECISIONS - Yasintha B. Z. Patty; Titis Puspaningrum Dewi Kartika (Reviu Accounting, Business & Organizations, 2025)
Research Objective – This research aims to determine the influence of Financial Performance in the form of the Degree of Fiscal Decentralization Ratio, PAD Effectiveness Ratio and Regional Financial Dependency Ratio on the Allocation of Capital Expenditures in the Sikka Regency Government for 2020 - 2022. Method - This type of research is quantitative with an associative approach. The population in this research is the Revenue Budget of East Nusa Tenggara Province for the 2020 - 2022 Fiscal Year where the Report on the Realization of Regency and City Regional Revenue and Expenditure Budgets in East Nusa Tenggara Province for 2020 - 2022 is taken as the research sample. Data analysis techniques use regretion analysis and statistical analysis with the help of the SPSS program. Findings - The results of this research indicate that the Degree of Fiscal Decentralization (X1) has no effect on Capital Expenditure Allocation (Y), the Effectiveness of Regional Original Income (X2) has an effect on Capital Expenditure Allocation (Y), and Regional Financial Dependence (X3) has no effect on Capital Expenditure Allocation (Y). Theoretical and Policy Implications - The implication of these findings is that capital expenditure allocation does not depend on regional finances and fiscal decentralisation in NTT. Research Novelty - The results of this study prove that capital expenditure allocation is highly dependent on the effectiveness of local revenue management and subsequent research  can examine the influence of external factors, such as political and economic factors, on capital expenditure allocation.